Improvements in concentration, working memory and sustained attention following consumption of a natural citicoline–caffeine beverage. (December 2014) - Bruce, Steven E.; Werner, Kimberly B.; Preston, Brittany F.; Baker, Laurie M.
Abstract This study examined the neurocognitive and electrophysiological effects of a citicoline–caffeine-based beverage in 60 healthy adult participants enrolled in a randomized, double-blind, placebo-controlled trial. Measures of electrical brain activity using electroencephalogram (EEG) and neuropsychological measures examining attention, concentration and reaction time were administered. Compared to placebo, participants receiving the citicoline–caffeine beverage exhibited significantly faster maze learning times and reaction times on a continuous performance test, fewer errors in a go/no-go task and better accuracy on a measure of information processing speed. EEG results examining P450 event-related potentials revealed that participants receiving the citicoline–caffeine beverage exhibited higher P450 amplitudes than controls, suggesting an increase in sustained attention. Overall, these findings suggest that the beverage significantly improved sustained attention, cognitive effort and reaction times in healthy adults. Evidence of improved P450 amplitude indicates a general improvement in the ability to accommodate new and relevant information within working memory and overall enhanced brain activation.